American Society of Hematology 2020 guidelines for sickle cell disease: transfusion support - Chou, Stella T.; Alsawas, Mouaz; Fasano, Ross M.; Field, Joshua J.; Hendrickson, Jeanne E.; Howard, Jo; Kameka, Michelle; Kwiatkowski, Janet L.; Pirenne, France; Shi, Patricia A.; Stowell, Sean R.; Thein, Swee Lay; et al. (Blood advances, 2020)
In July 2022, these guidelines were reviewed by an expert work group convened by ASH. Review included limited searches for new evidence and discussion of the search results. Following this review, the ASH Committee on Quality agreed to continue monitoring the supporting evidence rather than revise or retire these guidelines at this time. Limited searches and expert review will be repeated annually going forward until these guidelines are revised or retired. Background: Red cell transfusions remain a mainstay of therapy for patients with sickle cell disease (SCD), but pose significant clinical challenges. Guidance for specific indications and administration of transfusion, as well as screening, prevention, and management of alloimmunization, delayed hemolytic transfusion reactions (DHTRs), and iron overload may improve outcomes. Objective: Our objective was to develop evidence-based guidelines to support patients, clinicians, and other healthcare professionals in their decisions about transfusion support for SCD and the management of transfusion-related complications. Methods: The American Society of Hematology formed a multidisciplinary panel that was balanced to minimize bias from conflicts of interest and that included a patient representative. The panel prioritized clinical questions and outcomes. The Mayo Clinic Evidence-Based Practice Research Program supported the guideline development process. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to form recommendations, which were subject to public comment. Results: The panel developed 10 recommendations focused on red cell antigen typing and matching, indications, and mode of administration (simple vs red cell exchange), as well as screening, prevention, and management of alloimmunization, DHTRs, and iron overload. Conclusions: The majority of panel recommendations were conditional due to the paucity of direct, high-certainty evidence for outcomes of interest. Research priorities were identified, including prospective studies to understand the role of serologic vs genotypic red cell matching, the mechanism of HTRs resulting from specific alloantigens to inform therapy, the role and timing of regular transfusions during pregnancy for women, and the optimal treatment of transfusional iron overload in SCD.